A caracterização das atividades da coordenação de curso como uma prática social de gestão: um estudo com coordenadores de cursos da área de ciências sociais aplicadas de centros universitários de Belo Horizonte - Alexandre Ferreira Rolim (2004)
From the year of 1996, the Ministry of the Education and Culture started to supervise the education system federal, that is composed for the public and private institutions of superior education. So that the course gets a good note, it is necessary that the course coordinator has the capacity to exert managerial activities, what transforms it into a true manager of the superior course. Different theoretical perspectives concerning the management exist. Amongst them, it can be cited theperspective technique, the politics and the critical one. In the first one of them, the manager is seen as a rational instrument to reach daily pay-definitive and predominantly instrumental values, that have as performance strategy the valuation of the effectiveness of the organizational configuration. Already in the perspective politics, the management is seen as a process directed for the regulation of theconflict, in which the manager abdicates of the controller position and starts to interact with the team. The critical perspective, in turn, analyzes the management as being a mechanism of control, whose main function is to satisfy to the demands imposed for the way of capitalist production, with intention to propagate this ideology. Reed (1997) argues that these forms of practical analysis are incapable to perceive the reality of the managerial ones with the had depth and considers, then, one fourthperspective of analysis, called for it of praxeological perspective, in which the management is seen as a practical specific type of social. This perspective of analysis of the management possess three advantages on the previous perspectives: it provides a conceptual synthesis on aspects that in the previous boarding were seen separately; it rejects the treatment most orthodox of the management processes, which submit all the aspects of the social interaction to the imperatives ideological technician, politicians and; e provides an integrated theoretical picture,that becomes possible the relation enters the levels of organisational analysis, institutional and managing dodging itself of the functionalist and deterministically analysis, for which the perspectives previously cited seem to tend, when collated with the inherent complexity to the management processes. This research is an analytical descriptive study whose objective is to characterize the management activity of thecourse coordinator as one practical social one of management. This characterization implies in saying that the course coordinators possess activities that they search to conjugate practical the educative ones in and structures that possess one definitive degree of coherence and that the activity of coordination cannot be analyzed only under the perspective of a management model and contributes for the construction of the craft of course coordinator. For in such a way a research by means ofstructuralized half interviews with coordinators of course of the area of applied social sciences of the university centers of Belo Horizonte was carried through, that possess a qualitative boarding of data analysis.